Direct observation by high resolution transmission electron microscopy of gold(iii) particle transformation during aging reduction reaction. (11th October 2022) - Ferguson, Michael; Richard, Austin J.; Valdez, Jesus; Fiss, Blaine G.; Titi, Hatem M.; Provatas, Nikolas; Friščić, Tomislav; Moores, Audrey
Abstract : We use a gold nanoparticle synthesis as a model system to study the morphological and compositional changes in gold(iii ) precursor particles, while reduction is taking place during aging after mechanical activation. Abstract : We use a gold nanoparticle synthesis as a model system to study the morphological and compositional changes in gold(iii ) precursor particles, while reduction is taking place during aging after mechanical activation. Scanning transmission electron microscopy coupled with a high-angle annular dark field detector revealed the nanoscale changes in particle morphology, while electron energy loss spectroscopy mapped the changes in the chemical landscape during the reduction process. Tracking a specific region of interest on the sample grid allowed for comparisons to be made of the same particles across a two day monitoring period. High-angle annular dark field images permitted the visualization of particle size reduction of the gold salt while electron energy loss spectroscopy captured the surprising mobility of the lighter chlorine and sodium ions in a solid matrix during the reduction process. This system offers unique insight into precursor particle reactivity in the solid phase, which is relevant for many mechanochemical and aging-based reactions.